Las migraciones en el contexto internacional - Rodríguez Manzano, Irene (Revista Española de Desarrollo y Cooperación, 2023)
Despite being at the core of the international agenda, there are many ideas related to migration subjects that don’t fit in with empirical evidence. From an analytic perspective, this article refute some of these perceptions, as, for instance, that migration only flows from South to North or that we face an increase in migration.